“Weaponizing” The Tort of Family Violence? Myths, Stereotypes, Lawyers’ Ethics and Access to Justice - Sowter, Deanne; Koshan, Jennifer (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice)

(untitled) (Faculty of Law, University of Windsor, 2024)
Intimate partner violence [IPV] causes myriad and gendered harms, but Canadian law has inconsistently provided avenues of economic redress. Although tort law has evolved to allow IPV survivors to seek compensation, tort-based remedies are sought rarely and largely limited to intentional torts such as assault, battery, and the intentional infliction of emotional distress. These torts do not always encompass the harms sustained by IPV survivors, particularly those caused by economic abuse and coercive control. In Ahluwalia v Ahluwalia, a 2022 family law case, Justice Renu Mandhane responded to this gap in the law by recognizing a new tort of family violence, but her decision was overturned by the Ontario Court of Appeal in 2023, and the case is now before the Supreme Court of Canada. Our paper provides a feminist analysis of the role of tort law in providing compensatory remedies for survivors of IPV. We situate tort remedies and Ahluwalia within the wider context of Canadian laws addressing IPV and feminist critiques of tort law and theory. This wider context raises issues about access to justice and socio-economic responses to IPV for members of marginalized groups in particular. We also examine how myths and stereotypes have influenced this area of law and the role of lawyers and judges in this respect, including in Ahluwalia. We conclude that recognition of the tort of family violence is an important but limited step forward in compensating the harms of IPV, and we urge governments to do more to systemically remediate these harms.